2017
DOI: 10.1080/14767058.2017.1297411
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia in Jordan: incidence, risk factors, and its associated maternal and neonatal outcomes

Abstract: The overall incidence rate of preeclampsia was 1.3%. Preeclampsia was significantly associated with maternal and neonatal morbidity and mortality as well as increasing vaginal operative delivery, cesarean section, LBW, and birth asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
40
5
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 20 publications
14
40
5
12
Order By: Relevance
“…In addition to the family history of PE, the logistic regression analysis showed that primiparous women present an increased risk of nineteen times to develop PE when compared to women with more than two pregnancies. These results are similar to those by Khader et al, 18 observed that women in Jordanian had a twice the increased risk in developing PE in the first pregnancy than in later ones. Hernandez-Dias et al 19 also showed that multiparous women with no history of PE had a 1% risk of developing the disease, while women with PE in one or two consecutive pregnancies presented a 15-30% risk of recurrence, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the family history of PE, the logistic regression analysis showed that primiparous women present an increased risk of nineteen times to develop PE when compared to women with more than two pregnancies. These results are similar to those by Khader et al, 18 observed that women in Jordanian had a twice the increased risk in developing PE in the first pregnancy than in later ones. Hernandez-Dias et al 19 also showed that multiparous women with no history of PE had a 1% risk of developing the disease, while women with PE in one or two consecutive pregnancies presented a 15-30% risk of recurrence, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In their study, Khader et al (22) reported that the incidence of preeclampsia was high in pregnant women with a gestational age of ≤31 weeks. In our study, we found that the gestational week was lower in the HDP group than the control group and that the low gestational week was a risk factor for preeclampsia.…”
Section: Discussionmentioning
confidence: 97%
“…We could not find any literature examining the relationship between gravida and preeclampsia. In most of the studies in the literature, parity and primiparity-multiparity status were examined for preeclampsia (1,10,13,21,22). The fact that patients with high gravida are older, and the possibility of comorbidity increases with older age may cause preeclampsia to be seen more frequently in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la culminación de parto, el 97,8 % de los partos de las preelampticas fueron por cesáreas de emergencia (OR: 43,13, CI 95 %: 22,52 -84,56 y p < 0,001), dicho resultado es semejante a lo encontrado por Suarez (8). La cesárea se utilizó con mayor frecuencia entre las pacientes con preeclampsia en el 59,3 %, además representaron 5.5 más probabilidades de presentar parto pre término en el estudio de García (14).…”
Section: Discussionunclassified